The Meaning of Tolerance in K. H. A. Hasyim Muzadi’s Speech at the Presidential Palace: A Critical Discourse Analysis - FEBRI TAUFIQURRAHMAN (ELT-Lectura, 2017)
Conflicts of ethnicity and religions that recently occurred in Indonesia portrayed that the concept of tolerance built over the years is getting to be forgotten. Currently, the occurance of polarization results the dispute of having mutual superior feeling among groups. Intolerance does not only occur among inter-religious groups, but also occur between community organizations (ormas), football supporter, political organizations, to the House of Representatives member both national and regional levels. This study aims to find the meaning of tolerance expressed in K. H. A. Hasyim Muzadi speech at the Presidential Palace. The qualitative method is used by using critical discourse analysis approach. Through analysis of clause transitivity and the rules of macro, researchers found macro propositions that contain the meaning of tolerance. Those macro propositions represented in the topics of justice, management of economy, law, and social, protection and freedom in religion, self-integrity and social, economic and law justice, nationalism.